Pressure‐Dependent Effect of Hydrogen Adsorption on Structural and Electronic Properties of Pt/γ‐Al2O3 Nanoparticles. Issue 1 (15th November 2013) - Mistry, Hemma; Behafarid, Farzad; Bare, Simon R.; Roldan Cuenya, B.
Abstract Understanding the interaction of hydrogen with subnanometer platinum nanoparticles (NPs) under industrially relevant conditions is of great importance to heterogeneous catalysis. In this work, we investigate the pressure‐dependent changes in hydrogen coverage on size‐ and shape‐selected Pt/γ‐Al2O3 NPs by in situ X‐ray absorption near‐edge structure (XANES) analysis. Difference XANES calculations revealed an increase in the H/Pt ratio from 1.9 to 2.5 upon increasing the hydrogen pressure from 1 to 21 bar at room temperature (1 bar=100 kPa). In addition, extended X‐ray absorption fine structure measurements of the local geometrical structure showed changes in PtPt bond length and coordination number, revealing a morphological transformation in the NPs from a 2 D to a 3 D shape under increasing H2 pressure at room temperature. Such shape evolution leads to a decrease in the NP–support contact area and is thus expected to affect the NP stability against coarsening.